Characterisation and Properties of Lithium Disilicate Glass Ceramics in the SiO2-Li2O-K2O-Al2O3 System for Dental Applications - Naruporn Monmaturapoj; Pornchanok Lawita; Witoon Thepsuwan (Advances in Materials Science and Engineering)
This work proposes four different glass formulas derived from the SiO2-Li2O-K2O-Al2O3 system to investigate the effect of glass composition on their crystal formations and properties. Glass LD1 was SiO2-Li2O-K2O-Al2O3 system with the addition of P2O5 and CaF2 as nucleating agents. In Glass LD2, a slight amount of MgO was mixed in order to increase the viscosity of the melting glass. Finally, the important factor of Si : Li ratio was increased in Glasses LD3 and LD4 with compositions otherwise the same as LD1 and LD2. The results found that P2O5 and CaF2 served as a nucleating site for lithium phosphate and fluorapatite to encourage heterogenous nucleation and produce a fine-grained interlocking microstructure of lithium disilicate glass ceramics. MgO content in this system seemed to increase the viscosity of the melting glass and thermal expansion coefficient including the chemical solubility. Increasing the Si : Li ratio in glass compositions resulted in the change of the microstructure of Li2Si2O5 crystals.